WEBSITES FOR THE STUDY OF WICCA, WITCHCRAFT, AND MODERN PAGANISM. - Emerich, Monica M. (Religious Studies Review (Wiley-Blackwell), 2006)
The article reviews several web sites for the study of wicca, witchcraft and modern paganism including Adherents.com, The Pagan Federation, and The Witches' Voice.